Cancer and circulatory disease risks in US radiologic technologists associated with performing procedures involving radionuclides. Issue 11 (28th July 2015) - Kitahara, Cari M; Linet, Martha S; Drozdovitch, Vladimir; Alexander, Bruce H; Preston, Dale L; Simon, Steven L; Freedman, D Michal; Brill, Aaron B; Miller, Jeremy S; Little, Mark P; Rajaraman, Preetha; Doody, Michele M
Abstract : Objectives: The number of nuclear medicine procedures has increased substantially over the past several decades, with uncertain health risks to the medical workers who perform them. We estimated risks of incidence and mortality from cancer and circulatory disease associated with performing procedures involving the use of radionuclides. Methods: From a nationwide cohort of 90 955 US radiologic technologists who completed a mailed questionnaire during 1994–1998, 22 039 reported ever performing diagnostic radionuclide procedures, brachytherapy, radioactive iodine therapy, or other radionuclide therapy. We calculated multivariable-adjusted HRs and 95% CIs for incidence (through 2003–2005) and mortality (through 2008) associated with performing these procedures. Results: Ever (versus never) performing radionuclide procedures was not associated with risks for most end points examined. However, we observed increased risks for squamous cell carcinoma of the skin (HR=1.29, 95% CI 1.01 to 1.66) with ever performing diagnostic radionuclide procedures, for myocardial infarction incidence (HR=1.37, 95% CI 1.10 to 1.70), all-cause mortality (HR=1.10, 95% CI 1.00 to 1.20) and all-cancer mortality (HR=1.20, 95% CI 1.01 to 1.43) with ever performing brachytherapy, and for mortality from all causes (HR=1.14, 95% CI 1.01 to 1.30), breast cancer (HR=2.68, 95% CI 1.10 to 6.51), and myocardial infarction (HR=1.76, 95% CI 1.02 to 3.04) with ever performing other radionuclide therapy procedures (excluding brachytherapy and radioactive iodine); increasing risks were also observed with greater frequency of performing these procedures, particularly before 1980. Conclusions: The modest health risks among radiologic technologists performing procedures using radionuclides require further examination in studies with individual dose estimates, more detailed information regarding types of procedures performed and radionuclides used, and longer follow-up.